Perceived information literacy among undergraduate medical students at a Malaysian public university - Farah Norizwani Mohamad Maidin; Chui, Ping Lei; Che, Chong Chin; Lai, Lee Lee; Ranita Hisham (Malaysian Journal of Library and Information Science, 2022)
Information literacy competency is a crucial asset in the pursuit of knowledge for university students. It is the basis of student-centered learning and the key to academic success. Thus, assessment of students’ information literacy will help to enlighten the learning needs of the student in searching, managing, and applying information in the digital era. This study aims to assess the perceived information literacy skills among undergraduate students in the Faculty of Medicine of a public university in Kuala Lumpur. A cross-sectional study was conducted from June to August 2019. The Seven Pillars of Information Skills (SCONUL) was adopted for the measurement of information literacy skills in the present study. The seven pillars are identify, scope, plan, gather, evaluate, manage and present. A total of 315 completed questionnaires consists of four parts: the frequency of searching for information resources; perceived information literacy skills; source of learning and barrier in seeking information. About three-quarters of the students reported a high level of perceived information literacy skills. Among four information literacy domains, literacy on information search is at top of the rank, followed by information communication and dissemination, information processing, and information evaluation. The most frequently searched information resource used was the Internet search engine. The most common source of learning was an information literacy course and, the most common barrier was a limited subscription of full texts article. The students should be encouraged to obtain information from trusted resources such as library online subscribed databases. The students must advance their literacy in information processing and information evaluation. The findings also help to guide the University Library in planning the content for information literacy workshops.